2014
DOI: 10.4028/www.scientific.net/msf.806.89
|View full text |Cite
|
Sign up to set email alerts
|

High Quality Graphene Formation on 3C-SiC/4H-AlN/Si Heterostructure

Abstract: The growth of graphene on 3C-SiC/Si heterostructure is a promising approach, which provides low production cost, high scalability and easiness of nanoelectromechanical system fabrication. However, the quality of graphene is still insufficient for device applications due to mediocre morphological and structural quality of the 3C-SiC epilayers compared to bulk SiC crystals and to excessive Si out-diffusion from the Si substrate. Here, we propose a solution of inserting a 4H-AlN layer between 3C-SiC and Si, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Several works have been made on the SiC heteroepitaxy on AlN [9][10][11][12][13] and a few others focused also on graphene/SiC/AlN/Si(111) and graphene/SiC/AlN/Si(100) multilayer structures. 14,15) Furthermore, AlN layers have successfully prevented the formation of hollow voids during the SiC or graphene growth. [13][14][15] However, the rough surfaces of the abovementioned multilayers impeded the realization of novel highspeed transistors utilizing graphene with ultrahigh carrier mobility as a channel material.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several works have been made on the SiC heteroepitaxy on AlN [9][10][11][12][13] and a few others focused also on graphene/SiC/AlN/Si(111) and graphene/SiC/AlN/Si(100) multilayer structures. 14,15) Furthermore, AlN layers have successfully prevented the formation of hollow voids during the SiC or graphene growth. [13][14][15] However, the rough surfaces of the abovementioned multilayers impeded the realization of novel highspeed transistors utilizing graphene with ultrahigh carrier mobility as a channel material.…”
Section: Introductionmentioning
confidence: 99%
“…14,15) Furthermore, AlN layers have successfully prevented the formation of hollow voids during the SiC or graphene growth. [13][14][15] However, the rough surfaces of the abovementioned multilayers impeded the realization of novel highspeed transistors utilizing graphene with ultrahigh carrier mobility as a channel material. [13][14][15] The lattice mismatch between wurtzite AlN(0001) and Si(111) surfaces is ∼19%, 16) which is somewhat smaller than that between 3C-SiC(111) and Si(111) surfaces (∼20%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, a number of works demonstrating the feasibility of graphene synthesis on β-SiC/Si wafers of different orientations have been published . Mostly, these studies have been conducted on β-SiC (111) thin films [51][52][53][54][55][56][57][58][59][60][61][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] and single-crystalline SiC (111) wafers [62][63][64]. However, some studies have been carried out on β-SiC(001) [50, 61, 82-93, 101, 102] and even on polycrystalline β-SiC substrates [94].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] It has been reported that AlN immediate layers grown on Si substrates play a critical role in suppressing the Si outdiffusion during the SiC and graphene growth. [13][14][15][16] We have recently conducted the growth of 3C-SiC(111) on a 2H-AlN(0001) intermediate layer on an on-axis Si(110) substrate to form graphene on the SiC/AlN/Si substrate. 17) The use of the AlN intermediate layer proved to eliminate the problem of the formation of voids during the SiC and graphene growth.…”
Section: Introductionmentioning
confidence: 99%